(untitled) (European Bison Conservation Newsletter, 2010)
The prevalence of antibodies to Neospora caninum was examined in European bison (Bison bonasus bonasus L.) living in Białowieża, Poland. Sera of 67 European bison selected and shot or immobilized in 2009 and up to March 2010, of various ages and sexes, were tested for N. caninum antibodies using ELISA test. Positive antibody responses were found in 9 bison (prevalence 13,43%). Additionally, all positive sera were tested by Western blot to verify the ELISA results. The Western blot results confirmed the presence of antibodies to Neospora tachyzoites antigens in all tested ELISA positive sera. Our results indicate strongly the presence of N. caninum in the European bison in Poland. Farther studies are in progress to evaluate the existence of a sylvatic cycle of N. caninum.